Perceived Effectiveness of Virtual Mentoring and Coaching on Teachers’ of ELL’s Pedagogical Practices During COVID19 - Singer, Erin A.; Irby, Beverly J.; Pugliese, Elisabeth; Elfaragy, Hamada; Lara-Alecio, Rafael; Tong, Fuhui (European Scientific Journal, ESJ, 2022)
The purpose of this mixed methods study was to determine teachers’ perceptions of Project Massive Open Online Professional Individualized Learning (MOOPIL) Virtual Professional Development and the role it played in their pedagogical practices as they transitioned from face-to-face to online instruction during the initial months of the COVID-19 pandemic. We applied a mixed method approach to understand the experiences of educators engaged in virtual professional development, virtual mentoring and coaching, and an online learning community during a global pandemic in the Spring of 2020. Participants reported various ways Project MOOPIL impacted their experiences as educators. Teachers’ personal experiences in online learning through Project MOOPIL provided insight into the comparable experiences of students who were immersed in online education as well. Teachers reported a successful transfer of knowledge from this experience to their new distance learning domains that not only catered to the needs of ELs in their classes but to native English speakers as well. Furthermore, through their participation in VPLCs and engagement in Project MOOPIL VMC, participants demonstrated the ability to access and benefit from virtual collaborative support even when life got challenging. In this study, we examined virtual professional development intersectionality, distance learning, and the needs of emergent English speakers.